Mach Number Scaling of Foreshock Magnetic Fluctuations at Quasi-parallel Bow Shocks and Their Role in Magnetospheric Driving Throughout the Solar System - Brandon L. Burkholder; Li-Jen Chen; Katariina Nykyri; Norberto Romanelli; Menelaos Sarantos; Dave Sibeck; Jaye Verniero; Gina A. DiBraccio; Daniel Gershman; Martin Lindberg; Erin Kincade (The Astrophysical Journal)
Upstream of quasi-parallel bow shocks, reflected ions generate ion–ion instabilities. The resulting magnetic fluctuations can advect through the shock and interact with planetary magnetospheres. The amplitude of magnetic fluctuations depends on the strength of the shock, quantified by the Alfvén Mach number ( M _A ), which is the ratio of solar wind velocity to the local Alfvén velocity. With increasing heliocentric distance, the solar wind M _A generally increases, such that Mercury typically experiences a lower M _A ∼ 5 compared to Earth ( M _A ∼ 8), and Mars a slightly higher M _A ∼ 9. Farther out in the solar system, Saturn has even higher M _A (∼10). However, the solar wind flow is highly irregular, and on top of solar cycle variations these values for average M _A at each planet do not capture extreme events. Statistical analysis of OMNIWeb observations from 2015 to 2023 shows that sustained (30 minutes or more) high M _A (30–100) occurs at Earth about once a month. Using a selection of events in the ion foreshock regions of Mercury, Earth, Mars, and Saturn, a linear scaling is calculated for the maximum magnetic fluctuation amplitude as a function of M _A . The resulting slope is ∼0.2. Based on the dominant fluctuation frequency for the largest-amplitude events at each planet, it is found that Mars exists in a special regime where the wave period of the magnetic fluctuations can be similar to or longer than the magnetospheric convection timescale, making Mars more susceptible to space weather effects associated with foreshock fluctuations.